2022
DOI: 10.1242/jeb.244102
|View full text |Cite
|
Sign up to set email alerts
|

Hungry or angry? Experimental evidence for the effects of food availability on two measures of stress in developing wild raptor nestlings

Abstract: Food shortage challenges the development of nestlings; yet, to cope with this stressor, nestlings can induce stress responses to adjust metabolism or behaviour. Food shortage also enhances the antagonism between siblings, but it remains unclear whether the stress response induced by food shortage operates via the individual nutritional state or via the social environment experienced. In addition, the understanding of these processes is hindered by the fact that effects of food availability often co-vary with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In red kites, food supplementation during the nestling period mainly affected survival of nestlings and growth rate during the exponential part of the growth curve, rather than the final fledging body mass (Nägeli et al, 2022 ). Nonetheless, we recently showed that the feeding treatment strongly influenced the stress physiology of red kite fledglings (Catitti et al, 2022 ). Thus, our results suggest that condition‐dependent departure decisions in red kites are due to physiological components of body condition rather than due to the body mass component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In red kites, food supplementation during the nestling period mainly affected survival of nestlings and growth rate during the exponential part of the growth curve, rather than the final fledging body mass (Nägeli et al, 2022 ). Nonetheless, we recently showed that the feeding treatment strongly influenced the stress physiology of red kite fledglings (Catitti et al, 2022 ). Thus, our results suggest that condition‐dependent departure decisions in red kites are due to physiological components of body condition rather than due to the body mass component.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental food supplementation represents a valid approach to investigate condition‐dependent dispersal behavior (Fattebert et al, 2019 ; Kapota et al, 2016 ); the additional food is well known to increase body condition (e.g., Bańbura et al, 2011 ; Catitti et al, 2022 ; Ruffino et al, 2014 ). However, it also allows for disentangling the effect of spatial food gradients at natal sites from other environmental gradients on dispersal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Productivity varied strongly between years and nestlings were in better condition in years with enhanced productivity. Possible reasons causing temporal variability are variation in food supply (Gottschalk et al 2015, Catitti et al 2022, Nägeli et al 2022), notably the availability of voles (Gottschalk et al 2015), rainy weather (Nägeli et al 2022) and nest predation by goshawks Accipiter gentilis or raccoons Procyon lotor , with the latter varying more in space than in time (Gottschalk et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Productivity and population density in raptors often have strong links to food abundance (Houston and Schmutz 1995, Salamolard et al 2000, Rooney et al 2015), and the red kite is no exception. Empirical studies have shown that food supply positively affects red kite productivity (Gottschalk et al 2015), and nestling food supplementation experiments revealed that growth and condition of nestlings are reduced and their stress levels increased when food is short (Catitti et al 2022, Nägeli et al 2022). We found a positive correlation between productivity and nestling condition suggesting that under high food availability, more nestlings of a nest survive, and they are in good condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation